Surgical reduction of the renal mass in rats: morphologic and functional analysis on the remnant kidney - Santos,Luiz Sérgio (2006)
PURPOSE: This study has analyzed the giochemical and morphological effects on the remmant kidney in rats which were submitted to progressive surgical ablation of renal mass. METHODS: Sixty Wistar male rats, weighing between 210 and 380g, were used and they were distributed in 3 groups of 20 animals each. The rats from the groups called 1, 2 and 3 were submitted to the surgical removal of renal tissue equivalent to ½, 2/3 and 5/6 of the whole renal mass, respectively. Then the groups were subdivided into 2 subgroups and they were operated again within 24 hours (subgroups 1B, 2B and 3B) and within 8 weeks (subgroups 1C, 2C and 3C) for the removal of the remnant kidney. 24-hour urine and blood were collected to analyze serum creatinine, clearance of creatinine and proteinuria in the first surgical intervention and at the time of the re-operation. The remnant kidney was submitted to a macroscopic evaluation for the degree of hypertrophy and to the analysis of histology. RESULTS: There was a significant increase of the volume of the remnant kidney (164%) and glomerular sclerosis was present in 40% of the animals submitted to the ablation of 5/6 of renal mass. Functional alterations characterized by the increase of urinary excretion of proteins (50% in group 3), rise in the serum creatinine (261% subgroup 2B; 371% subgroup 3B, 118% subgroup 3C) and a significant reduction of the clearance of creatinine (control x subgroup 3C = 2,88 x 1,15 ml/min: p<0,05 were also observed. CONCLUSION: The compensatory renal hypertrophy, as well as the glomerular injury translated in the form of proteinuria and sclerosis, are closed related to the volume of the remnant kidney, thus they are more evident when a greater fraction of the renal tissue is excised.